1993
DOI: 10.1159/000239117
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia Resulting from Prostatic Surgery in Patients with or without Preoperative Bacteriuria under Perioperative Antibiotic Use

Abstract: We investigated the source of organisms detected in blood specimens obtained during and immediately following prostatic surgery under perioperative antibiotic use, as related to the results of cultures of preoperative urines and prostatic tissues. Ninety patients with benign prostatic hyperplasia were studied. The incidence of bacteremia was 28.9%: 53.7% in patients with preoperative bacteriuria and 8.2% in those without bacteriuria, a significant difference (p < 0.01). Of these bacteremic patients, 5, who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
(31 reference statements)
2
11
1
3
Order By: Relevance
“…All five patients were bacteriemic as determined by blood culture, which was taken during or immediately after prostatectomy. In the same study, the authors recommended starting antimicrobials at least 12 to 24 hours pre-intervention [20]. Although bacteraemia was not evaluated in our study, we did not encounter any severe infectious complications such as sepsis postoperatively when administering antibiotics only 30 to 60 minutes before a surgical procedure.…”
Section: Urological Proseduresmentioning
confidence: 71%
See 2 more Smart Citations
“…All five patients were bacteriemic as determined by blood culture, which was taken during or immediately after prostatectomy. In the same study, the authors recommended starting antimicrobials at least 12 to 24 hours pre-intervention [20]. Although bacteraemia was not evaluated in our study, we did not encounter any severe infectious complications such as sepsis postoperatively when administering antibiotics only 30 to 60 minutes before a surgical procedure.…”
Section: Urological Proseduresmentioning
confidence: 71%
“…As a consequence of these potential problems, many researchers have recommended short-term antimicrobial therapy, the shortest of which starts immediately before the surgical procedure [8,13,[16][17][18][19]. Interestingly, despite the efficacy of this preoperative short-term therapy, it has been shown that transient bacteraemia can occur with earlier initiation of antimicrobial therapy [9,20]. To determine the optimal time for starting preoperative antimicrobial therapy, Murphy et al administered antibiotics at varying intervals before an operation.…”
Section: Urological Proseduresmentioning
confidence: 99%
See 1 more Smart Citation
“…They included preoperative factors (age, ASA III/IV patients, increased serum creatinine, lack of antibiotic prophylaxis, acute urine retention, preoperative catheter drainage, and preoperative bacteriuria) and postoperative factors (increased duration of catheterization, nonclosed drainage system) [1, 2, 8, 9, 10, 11, 12, 13]. The multivariate analysis performed in this study confirms that preoperative bacteriuria is a risk factor of postoperative infection and identified 2 other risk factors: a surgical procedure lasting more than 70 min, and the center where the procedure was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Estos factores están relacionados con el hospedero, la instrumentación del tracto urinario y el procedimiento en sí mismo (40). Entre los que se han planteado, se encuentran la bacteriuria asintomática, la edad, el puntaje ASA (American Society of Anesthesiologists), la historia de ITU previa a la cirugía, el uso de sonda vesical, el uso de antibioticoterapia antes de la cirugía, la clasificación de la herida quirúrgica, el índice de riesgo de la NNIS (National Nosocomial Infection Surveillance), la duración del procedimiento quirúr-gico, el tiempo de hospitalización y el de irrigación posoperatoria, la necesidad de manipulación de la vía urinaria, la desconexión del sistema cerrado de drenaje en el posoperatorio y el tiempo de uso del catéter uretral después de la cirugía (5,15,29,(46)(47)(48).…”
Section: Complicaciones Infecciosas De La Rtupunclassified